1998
DOI: 10.1111/j.1539-6924.1998.tb00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Worry and Risk Perception

Abstract: Risk perception is sometimes measured by means of judgments about worry, sometimes as perceived risk more directly. However, perceived level of risk calls for a more intellectual judgment and worry tends to refer to emotional reactions. These two are therefore not the same and need not be strongly correlated. Results reported here show that perceived risk and worry are indeed weakly correlated, both for generalized worry and for more specific measures of worry matched with the same hazard as risk ratings. A di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
218
5
14

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(255 citation statements)
references
References 28 publications
18
218
5
14
Order By: Relevance
“…Loewenstein et al 17 cited my previously published data on risk and worry 26 in support of their thesis that risk perception is a "feeling". The correlation between risk and worry in my study were of the order 0.3, and my conclusion was that risk and worry were largely independent.…”
Section: Discussionmentioning
confidence: 95%
“…Loewenstein et al 17 cited my previously published data on risk and worry 26 in support of their thesis that risk perception is a "feeling". The correlation between risk and worry in my study were of the order 0.3, and my conclusion was that risk and worry were largely independent.…”
Section: Discussionmentioning
confidence: 95%
“…Yet, the two Gallup questions, one for personal risk and the other for societal risk, are not comparable, since the personal risk question was phrased in terms of worry, not likelihood as the societal risk question. Perceived risk and worry have been found to be rather weakly related (Sjöberg, 1998).…”
Section: Sjöbergmentioning
confidence: 99%
“…Huddy et al found personal risk to have consequences mostly for personal risk management, not policy attitude (Huddy et al, 2002). Relatively little work has been done on worry (Baron et al, 2000;Drottz-Sjöberg and Sjöberg, 1990;Sjöberg, 1998), but it seems to be a quite a popular dimension among pollsters and opinion researchers, as exemplified by question G1 above. Some research results suggest that risk and worry make independent contributions to policy attitude (Myers et al, 1997).…”
Section: Anxiety Level Low Highmentioning
confidence: 99%
“…Risk perception is often considered to involve intellectual judgments; worry on the other hand involves emotional responses [3]. Risk perception is in general affected by different factors, for example is the risk perceived to be high when it is involuntary, uncontrollable, unfamiliar, dread and pose a high risk to future generations [4,5].…”
Section: Introductionmentioning
confidence: 99%